Multi-objective optimization of structured material parameters for reducing broadband aircraft noise across various frequencies - Kone, Tenon Charly; Ghinet, Sebastian; Panneton, Raymond; Grewal, Anant (Frontiers in Acoustics, 2025)
IntroductionControlling broadband noise across the entire frequency spectrum, from low to high frequencies, remains a critical challenge in aerospace, transportation, and construction industries. Current acoustic metamaterials are effective primarily for low-frequency noise but suffer from narrow-band resonances that limit their application for broader-band noise attenuation.MethodsThis study introduces an innovative structured material system comprising a parallel assembly of structured materials and Helmholtz Resonators embedded within a fiberglass layer. A multi-objective optimization approach based on a surrogate model was employed to fine-tune the parameters of each structured material. The optimization process allowed precise grouping of individual resonant frequencies, thereby broadening the effective resonance frequency band to address low- and high-frequency noise.ResultsThe proposed structured material system demonstrated significant broadband noise attenuation across a wide frequency range. The optimized configuration achieved effective noise reduction while adhering to practical implementation constraints, providing a feasible solution for industrial applications.DiscussionThis study underscores the importance of optimization in advancing noise control technologies. By overcoming the limitations of narrow-band resonances, the proposed approach achieves effective broadband noise attenuation, addressing critical challenges in aerospace, transportation, and construction. The integration of structured materials and Helmholtz Resonators, optimized using a surrogate model, broadens the resonance frequency band while meeting practical implementation requirements. These results highlight a viable and impactful solution for noise control across diverse industries.